African–American and Caucasian mortalities are the same after traumatic injury: pair matched analysis from a national data. Issue 1 (31st March 2020) - Ahmed, Nasim; Kountz, David; Kuo, Yenhong
Abstract : Background: African–Americans have worse outcomes than Caucasians in many clinical conditions studied, including trauma. We sought to analyze if mortality is different in these groups through analysis of a national data set. Methods: Recent data from the national Trauma Quality Improvement Program were assessed with analysis, including all African–American or Caucasian patients who were brought to level I or level II trauma centers for care. Propensity scores were calculated for each African–American patient using age, sex, Injury Severity Score (ISS), Glasgow Coma Scale (GCS), injury type, insurance information and American College of Surgeons trauma level. The primary outcome of this study was in-hospital mortality, and the secondary outcomes were hospital length of stay and discharge disposition. Results: A total of 82 150 (13.65%) out of 601 768 patients who qualified for the inclusion in the study were African–American. The remaining 519 618 (86.35%) were Caucasian. The median age (IQR) of the patients was 54 (33 to 72) years old, and approximately two-thirds of the patients were male. The median ISS and GCS score were 12 (9 to 17) and 15 (15 to 15), respectively. More than 90% of patients sustained blunt injuries. Overall, there was no significant difference found in overall in-hospital mortality between Caucasians and African–American patients (3% vs. 2.9%, p=0.2); however, the median (95% CI) hospital length of stay was 1 day longer in African–American patients compared with Caucasian patients (5 (5.5) vs. 4 (4.4), p<0.001). When the discharged destinations between the two groups were compared, a higher proportion of Caucasians were discharged to home without services (66% vs. 33%). Conclusion: Our study showed that trauma mortalites among African–American and Caucasians are the same. Efforts to mitigate the ethnic and racial biases in the delivery of healthcare should continue, and these results (no differences in mortality) should be validated in other clinical settings. Level of evidence: Level II.